Photovoltaic multimode charging with maximum power point tracking - Ramos, Niño Christopher B.
The configuration of a solar panel with a diode in series is a simple yet effective way of charging a battery. As soon as the solar panel voltage exceeds the battery voltage by a diode forward voltage drop, it will directly connect to the battery and start charging. This mode of charging is called direct mode and because of the very small loss that the diode generates during its direct mode of operation, the charging efficiency is around 93%. Maximum power point tracking is another method used to extract more power from the solar panels. There is a point in the solar panel's I-V curve called the maximum power point denoted by (Vmpp, Impp) where the product Vmpp ? Impp gives the maximum power(Pmax); however, the solar panels do not always operate at maximum power point whenever they receive sunlight. This problem is solved by a Maximum Power Point Tracker (MPPT) which controls a DC-DC converter to force the panels to operate at maximum power point. The configuration is able to match the panel with the load and maximize the transfer of power. The DC-DC converter must have a high efficiency so that the maximum power extracted from the solar panel will not suffer significant losses as they are delivered to the battery. One can further assess the performance of a photovoltaic charging system in terms of the amount of charge it can store at the battery at the end of the day. A charger with a buck-boost DC-DC converter may be less efficient than the solar panel with a series diode but it can extend its charging beyond peak hours of sunlight where the solar panel voltage is less that the battery voltage. A diode charge has a relatively shorter charging period but for sunny days where the operation is generally in direct mode, a diode charger may be preferred. Therefore a good photovoltaic charging system is one that can balance these trade-offs and extract the maximum energy possible from the solar panels. The project aims to increase the performance of a multimode charger[2] that integrates the features of a diode charger and a buck-boost charger by adding a microcontroller-based maximum power point tracking system. The multimode charger[2] is a non-commercial charger done by Marco L. Fernando in his research project entitled ?Photovoltaic Charging of a Lead-Acid Battery Using a Buck-Boost Converter?. The microcontroller will also be used to carry out the housekeeping of the systems such as preventing battery overcharging.